A physical modelling study of waveform amplification effects of reservoir heterogeneity on time‐lapse seismic attribute analysis. (21st December 2022) - He, Yan‐Xiao; Wang, ShangXu; Dong, Chunhui; Tang, Genyang; Zhang, Jialiang; Shi, Peidong; Feng, Zhanxun; Zhang, Fengqi; Liu, Junzhou; Li, Guofa; Shi, Lei
Abstract: Hydrocarbon depletion causes fluid saturation and pressure changes, resulting in perturbations in reservoir elasticities and, hence, observable time‐lapse (or 4D) seismic responses. Using controlled physical modelling experiments, we aim to evaluate reservoir heterogeneities‐related scattering effects on seismic signatures and assess pore‐fluid substitution impacts on the 4D seismic attributes. Physical modelling experiments reveal that wave propagations in heterogeneous rocks produce substantially magnified 4D attribute differences related to fluid replacements, contrary to seismic features in homogeneous rocks. In particular, reflected waveforms from the gas‐filled scenario exhibit more apparent discontinuities and amplitude variations than water‐ and oil‐saturated scenarios in the heterogeneous regions. It is interesting to see that fluid substitution‐induced 4D seismic differences are observable within the weakly heterogeneous region but significantly strong within the highly heterogeneous region. Although it is expected that substituting oil with water produces weak perturbations in reservoir elasticities, the 4D difference observations between time‐varying records are apparent. This implies that in addition to reservoir heterogeneities‐induced amplifying effects, 4D seismic anomalies are also caused by pore‐fluid changes. Due to mesoscopic rock heterogeneities, seismic responses are complicated, and 4D difference estimates will be amplified strongly and, thus, unable to quantify variations in fluid saturation appropriately. This implies that obvious difference volumes in the underburden regions do not necessarily correspond to significant variations in pore‐fluid. Subsequently, two end‐member rock physics models were applied to predict the widest range of velocity variations and pore‐fluid behaviours. Although mesoscopic heterogeneities cause varying degrees of difficulties for hydrocarbon detection, the deformed waveform‐induced seismic attribute anomalies, which are often greatly amplified, may be beneficial for more accurately identifying reservoir fluids and monitoring their minor variations in practice.